Dreams and the invisible world in colonial New England : Indians, colonists, and the seventeenth century - Plane, Ann Marie, 1964- (University of Pennsylvania Press, 2014)
Ann Marie Plane explores the significance of dreams in seventeenth-century life. Touching on race, gender, emotions, and interior life, this book treats colonist and Indian experiences and analyzes both the content of the dreams themselves and the act of dream reporting.